Pengaruh Penambahan Wortel dan Buncis terhadap Sifat Organoleptik dan Daya Terima Nugget Sitelcis - Rima Sulastri; Made Darawati; Ketut Swirya Jaya (Poltekkes Kemenkes Mataram, 2020)
Background : Utilization of Rice Snails (Pila ampullacea) in the Making of Nugget with the Addition of Vitamins and Minerals (Carrots and Beans) which Contain High Protein to Overcome Nutritional Problems of PEM (Protein Energy Lack) in Toddler Children. Objectives : To determine the effect of carrot and bean addition on organoleptic properties and acceptability of toddlers on the SITELCIS nugget (snail carrot snail). Research Methods: This study used an experimental method in the laboratory with a Completely Randomized Design (CRD) of 1 factor, namely the addition of Carrots and Beans. Performed 5 levels of treatment and repetition 3 times with the addition of different Carrots and Beans. Organoleptic Properties Test Using the hedonic test method. Research Results : Anova Statistical Test Results on Panelists (Tukey) Effect of Carrots and Beans on Flavor (p <0.05). While the parameters of color, aroma and texture have no effect or (p> 0.05). The most preferred treatment for the highest average score is the taste parameter in treatment t4 with the addition of carrots and beans 20%. Conclusion : Based on the results of the test results of the acceptance of the SITELCIS Nugget in toddlers aged 4-5 years at the level of treatment t4 with the addition of carrots and beans (20%). From the results of the acceptance of children under five with given per serving of nuggets, the intake of good intake (≥ 80%) as many as 22 people, while the receiving power is less (<80%), which is as many as 3 people.